Suvorexant: A boon for Sleepless Nights - Khadka, Anjan; Brashier, Dick; Khanpure, Amol Vijay; Chuki, Pem (Medical Journal of Shree Birendra Hospital, 2016)
Insomnia is characterized by difficulty in falling asleep, difficulty maintaining sleep, or experiencing nonrestorative sleep. Insomnia is the most common medical complaint in general practice. Low efficacy and various side effects limit the use of existing treatment option. Suvorexant is an orexin receptor antagonist (ORA), first in a new class of drugs in development for the treatment of insomnia. It inhibits the wakefulness-promoting orexin neurons of the arousal system thereby promoting the natural transition from wakefulness. It also improves sleep onset and sleep maintenance and has a favorable tolerability and limited side-effect profile.